The Influence of Consumer Engagement on Brand Social Media on Consumer Attitudes and Purchase Intentions of Local Fashion Products - Febina Amalia Putri; Anas Hidayat (Cita Konsultindo Research Center, 2024)
This study aims to see the influence of consumer engagement on brand social media on consumer attitudes and purchase intentions of local fashion products (shop at velvet). This study used a sample of 250 respondents and sampling using the convience sampling method. This study uses descriptive analysis and uses SmartPLS SEM in processing data. This study shows the results that (1) consumer engagement with brands on social media has a positive and significant effect on consumer attitudes (2) Consumer Engagement with Brands on Social Media has a positive and significant effect on Purchase Intent (3) Consumer Attitudes Towards a Brand's Social Media Presence have a positive and significant effect on Purchase Intent (4) Brand Familiarity has a positive and significant effect on Consumer Engagement with Brands on Social Media (5) The Quality of Brand Social Media Content Information has a positive and significant effect on Consumer Engagement with Brands on Social Media.